Pengaruh Konseling Antenatal terhadap Kepatuhan Pemeriksaan Kehamilan - Martha, Rizkika; Wulandari, Rini; Pertiwi, Inda (Primary Journal of Multidisciplinary Research, 2025)
Pregnancy is a physiological process accompanied by physical and psychological changes that require special attention to maintain the health of both mother and fetus. Antenatal care (ANC) is a health service aimed at early detection of risk factors, preventing complications, and preparing mothers for childbirth and the postpartum period. Although ANC has become a standard health service, many pregnant women are still noncompliant with recommended schedules, due to limited knowledge, low awareness, or lack of adequate information and support from health professionals.Antenatal counseling is an effective communication approach provided by health workers to improve understanding, motivation, and awareness among pregnant women in maintaining their health during pregnancy. This study aims to analyze the effect of antenatal counseling on compliance with antenatal care visits. The research employed a quasi-experimental design with a pre-test and post-test in the intervention group. The study sample consisted of pregnant women in the first to third trimester who met the inclusion criteria, totaling XX respondents, selected using purposive sampling. Data collection instruments included a compliance questionnaire and ANC records from maternal and child health books.The results showed a significant increase in compliance with antenatal care after antenatal counseling was given, with a p-value < 0.05. Pregnant women who received counseling demonstrated better understanding of ANC importance, greater motivation to attend according to schedule, and more positive attitudes toward pregnancy care. These findings confirm that antenatal counseling is an effective intervention to improve maternal compliance with ANC visits.Therefore, this study recommends that health professionals, particularly midwives, enhance the quality and frequency of antenatal counseling as part of routine maternal care. Such efforts are expected to reduce noncompliance rates, enable earlier risk detection, and ultimately decrease maternal and infant morbidity and mortality rates.